Money, myths, and change: the economic lives of lesbians and gay men - Badgett, Mary Virginia Lee (University of Chicago Press, 2001)
How does the standard of living of gay men and lesbians compare with that of heterosexuals? Do homosexuals make financial and family decisions differently? Why are the professional lives of gay men and lesbians dissimilar from those of heterosexuals? Or do they even differ? Have gay people benefited from the recent economic boom? Or have public policies denied them their fair share? Money, Myths, and Change provides new answers to these complex questions. This is the first comprehensive work to explore the economic lives of gays and lesbians in the United States. M. V. Lee Badgett weaves through and debunks common stereotypes about gay privilege, income, and consumer behavior. Studying the ends and means of gay life from an economic perspective, she disproves the assumption that gay men and lesbians are more affluent than heterosexuals, that they inspire discrimination when they come out of the closet, that they consume more conspicuously, that they enjoy a more self-indulgent, even hedonistic lifestyle. Badgett gets to the heart of these misconceptions through an analysis of the crucial issues that affect the livelihood of gay men and lesbians: discrimination in the workplace, denial of health care benefits to domestic partners and children, lack of access to legal institutions such as marriage, the corporate wooing of gay consumer dollars, and the use of gay economic clout to inspire social and political change. Both timely and readable, Money, Myths, and Change stands as a much-needed corrective to the assumptions that inhibit gay economic equality. It is a definitive work that sheds new light on just what it means to be gay or lesbian in the United States.
Section: xii, 302 pages ; 24 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; capitalisme; cours; discipline; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; shm4000; systèmes d'oppressions; thématiques; travail; états-unis

L’économie politique du sexe : transactions sur les femmes et systèmes de sexe/genre - Rubin, Gayle (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 1998)
La littérature sur les femmes — tant féministe qu’antiféministe — est une longue rumination quant à la nature et à la genèse de leur oppression et de leur subordination sociale. La question n’est pas sans importance, car les réponses qui lui sont données déterminent la manière dont nous envisageons l’avenir et si nous jugeons réaliste ou non d’espérer une société égalitaire entre les sexes. Plus important, l’analyse des causes de l’oppression des femmes fonde toute estimation de ce qu’il faudrait exactement changer pour réaliser une société sans hiérarchie de genre
Première publication: 1975 http://journals.openedition.org/cedref/171
Keywords: 1900-1999; 1960-1969; 1970-1979; anthropologie; approches et analyses; capitalisme; classe ouvrière; cours; discipline; europe; famille; fem1000; france; féminisme matérialiste; histoire et politique; inégalités; marxisme; patriarcat; premier cycle; psychanalyse; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences; sciences humaines; soc1016; soc2014; sociologie; systèmes d'oppressions; thématiques; théories féministes

Engels et l'émancipation des femmes - Europe Solidaire Sans Frontières - Trat, Josette (Engels et savants révolutionnaires, 1997)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1970-1979; approches et analyses; capitalisme; classe ouvrière; corps; cours; discipline; europe; famille; france; justice sociale; marxisme; premier cycle; périodes historiques; russie; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; travail